IMPORTANT DISEASES OF COCONUT IN INDIA - K. K. N. Nambiar; Rohini Iyer (International Coconut Community Journal, 1988)
Today India stands at the third position as far as the world situation of coconut production is concerned. Coconut occupies 1.1. million hectares of land producing 6,887 million nuts in this country. In the southern part of the country viz. Kerala, Kamataka, Tamilnadu and Andhra Pradesh, coconut is a very good source of income and these states account for most of the production of coconut. In spite of the importance it has in India's economy, the productivity of the crop is low. Although many factors are responsible for the poor yields, the most important of these are the diseases that attack these palms and affect their productivity. Among these diseases, a few are killers while others are slow and debilitating in nature. For some of them the cause is known while the aetiology of some others is still elusive. This review envisages in discussing some of the recent research trends in the major diseases of coconut in India.